Typ.ologies: Reframing Ireland’s vernacular letterform through the lens of heritage - Maher Ring, Dee (InfoDesign, 2023)
Since the late 1800s, vernacular letterforms have been vital components of the traditional shopfronts of Ireland, enlivening, place-making, and inspiring dialogue with streetscapes. The National Inventory of Architectural Heritage identifies, records, and evaluates Ireland’s post-1700 architectural heritage. While the state initiative appraises architecturally significant shopfronts, it typically overlooks the critical signage element. This research aims to bridge this gap by documenting, mapping, and interpreting the existing vernacular letterforms in Kilkenny as a paradigm. Through the lens of heritage, the study seeks to construct a case for preserving, promoting, and advocating for vernacular letterforms and the traditional craft of signwriting. Signwriting straddles art, craft, and design dissolving creative hierarchies yet remains academically underexplored. Raising awareness and advancing the craft’s criticality may influence local and national policy. With the current economic climate threatening to permanently alter Ireland’s typographic landscapes, academic scrutiny of this rich graphic heritage has never been more crucial.